Good Governance dalam Perspektif Hukum Islam - Rachman, Arief Aulia (Al-Manahij: Jurnal Kajian Hukum Islam, 2010)
Governance system refers to all systems in bureaucracy which conducts its role to order the citizen. The study of governance is not only talk about a little part of it, but it refers to all important elements in a state.